Endurance training and sprint performance in elite junior cross-country skiers - Sandbakk, O.; Welde, B.; Holmberg, H. C. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Sprint races in modern cross-country (XC) skiing have a shorter racing time, as well as a relatively flat terrain profile, when compared to traditional races. Several studies have thus suggested that maximal speed is the most important performance predictor (e.g. Stöggl et al., 2007). However, the energy release for comparable racing times in other sports is reported to be 70-85% aerobic (Gastin, 2001). The present study therefore investigated the importance of aerobic capacity in sprint performance. The effects of a major change in training stimuli, due to increased emphasis on high-speed moderate intensive endurance training upon sprint performance, maximal O2-uptake (VO2max) and O2-uptake at the ventilatory threshold (VO2VT) were also examined. Methods: Fifteen (10 males and 5 females) elite junior XC skiers (age 17.4±0.5 yr, VO2max 68±6 ml kg-1 min-1) participated in this study. After an eight week baseline training period, all subjects performed a freestyle 1.5 km sprint time-trial on roller skis. In addition, VO2max and VO2VT were measured in the laboratory. Thereafter, an eight week intervention training period was performed. Subjects were split into a control group (CG, n=8) and an intervention group (IG, n=7). The IG increased their training at intensities near the ventilatory threshold, emphasizing level and mixed terrain in order to induce more high-speed training, while the CG continued their traditional polarized training model with 70-80% slow distance training and the remainder as high-intensity interval training. After the intervention training period the sprint race and tests on VO2max and VO2VT, were rerun. Results: Close relationships were found between VO2max (r = -0.79, p<0.01) and VO2VT (r = -0.67, p<0.01) and sprint performance. The mean sprint time in all athletes was 3:36±0:19 min in the pre-test. The IG improved sprint performance by 4.5±2.9% (p<0.01), VO2max by 3.9±1.9% (p<0.01) and VO2VT by 9.9±3.1% (p<0.01) from pre- to post-test. No significant changes were found in the CG. Discussion: Our findings suggest an association between sprint performance and aerobic capacity. The improvements in the IG are potentially related to the major change in training stimuli and demonstrate the effects of training at these moderate intensities, as well as the importance of training periodization.